P810 Serious pulmonary infections in patients with inflammatory bowel disease on treatment with anti-TNF. (16th January 2018) - Algaba, A; Guerra, I; Guardiola, A; Bonillo, D; Granja, A; Bernal, P; Aller, M d M; Hernández, B; Aulló, C; Bermejo, F
Abstract: Background: Several studies have reported increased rates of serious infections in patients with IBD on anti-TNF. Our aim was to determinate the incidence and characteristics of pulmonary infections in patients with IBD on treatment with anti-TNF in our environment. Methods: Prospective, observational, 5-years follow-up study (2012–2017) in patients with IBD who were treated with anti-TNF in our hospital. Demographics data, IBD therapies, duration of anti-TNF treatment, and infection characteristics were collected. Results: A total of 756 patients with IBD were managed in our center. Of these, 133 received treatment with anti-TNF between 2012–2017 (110 CD, 21 UC, 2 IBD unclassified). Eleven patients with IBD on treatment with anti-TNF (8 CD, 3 UC) developed serious pulmonary infections during the period of the study (cumulative incidence=8.3%; 95% CI:3.2–13.3). There were 8 cases of pneumonia (diagnosed by radiographic findings, CI=6%; 1.6–10.4) and 3 cases of active pulmonary tuberculosis (diagnosed by CT and positive culture in biological samples, two of them disseminated, CI = 2.3%; 0.5–6.4). The infection incidence rate was 0.03% per patients-year of follow-up (0.016–0.059). The risk of develop an infection was not different in patients on IFX compared with those on ADA (RR:1.3; 0.4–5.65). At time of infection, the mean age was 47 ± 16 y, 54% women, 45% smokers and 36.4% were on combined therapy (anti-TNF+thiopurines). All patients reported symptoms before the diagnosis being the most common fever (72%), cough (63.5%) and chest pain (18.2%). Regarding the type of anti-TNF, 7 patients (63.6%) were on IFX, 3 (27.3%) were on ADA and 1 (9.1%) on golimumab. The mean time of anti-TNF therapy until the development of the infection was 48.2 months (IQR 5–72). After the diagnosis of infection, 5 patients (45.5%) withdrew temporarily the anti-TNF until the radiologic resolution of infection and four patients withdrew it definitely following medical criteria (36.4%). Five patients were hospitalised due to the infection. The three cases of active tuberculosis had a previous PPD skin test positive and received prophylaxis with isoniazid according to guidelines. All pneumonias were treated with levofloxacin 500 mg every 12/24 h during 7–10 days. Tuberculosis cases were treated with regimens without isoniazid during 8–12 months. All infections were resolved with treatment Conclusions: Pulmonary infections such as pneumonia and tuberculosis should be considered in patients under anti-TNF treatment when respiratory symptoms appear. It would be advisable an active follow-up in patients with previous PPD skin test positive by the risk of tuberculosis reactivation with anti-TNF, despite having made an appropriate prophylaxis. The prognosis of pulmonary infections was good in our series